A new cyrtochilum (orchidaceae: oncidiinae) from Sierra Nevada de santa marta in Colombia - Dalström, Stig (Universidad de Costa Rica, 2013)
A new species of Cyrtochilum from the isolated region of Sierra Nevada de Santa Marta in Colombia is described and illustrated, and compared with similar species. It is distinguished from other Cyrtochilum species by the violet color of the sepals and petals, in combination with the pandurate lip lamina with a large and protruding nose-like central callus keel.